2016
DOI: 10.1002/icd.1959
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of a Social Skills Training and Facilitated Play Early Intervention Programme for Extremely Shy Young Children in China

Abstract: The goal of this study was to provide a preliminary evaluation of a social skills and facilitated play early intervention programme to promote social interaction, prosocial behaviours and socio‐communicative skills among young extremely shy children in China. Participants were a sample of n = 16 extremely shy young children attending kindergarten in Shanghai, China. Children were randomly assigned to either the Social Skills Facilitated Play or comparison condition. Baseline, post‐intervention and 2‐month foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 32 publications
1
16
0
3
Order By: Relevance
“…Moreover, eight intervention studies involved special groups of participants (SG). These were, for example, children with emotional and/or behavioral disorders (Kellner et al., 2008; McKenney & Dattilo, 2001), disabilities (Davis, Langone, & Malone, 1996; Kroeger et al, 2007), and cognitive impairments (Hoff & Ronk, 2006) and aggressive (Leff, Waasdorp, & Paskewich, 2016) or shy children (Li et al., 2016). In one study, the participants were children of parents with depression (Solantaus et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, eight intervention studies involved special groups of participants (SG). These were, for example, children with emotional and/or behavioral disorders (Kellner et al., 2008; McKenney & Dattilo, 2001), disabilities (Davis, Langone, & Malone, 1996; Kroeger et al, 2007), and cognitive impairments (Hoff & Ronk, 2006) and aggressive (Leff, Waasdorp, & Paskewich, 2016) or shy children (Li et al., 2016). In one study, the participants were children of parents with depression (Solantaus et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of clinical practice, our findings support the recent trend among early intervention programs designed to assist extremely shy children to include a focus on improving social skills and facilitating social interactions (e.g., Chronis‐Tuscano et al., ). This has also included some promising preliminary results in China (Li et al., ). Our findings suggest that, among older children and adolescents, the peer group plays an increasingly complex and multifaceted role in the links between shyness and internalizing problems.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the primary aim of this study is to examine a complex conceptual model, involving both mediation and moderation, that links shyness, peer relations, gender, and internalizing problems in a sample of urban mainland Chinese young adolescents. A better understanding of the mediating and moderating factors implicated in the development and implications of shyness in China not only extends etiological models, but also aids in the design of effective early intervention programs (Li et al., ).…”
Section: Shyness In Chinamentioning
confidence: 99%
“…An initial evaluation of SSFP found increased observer-rated social behaviors at preschool compared to a waitlist control (WLC) group, though teachers did not report similar changes (Coplan et al, 2010). More recently, investigators reported similar benefits of SSFP participation in observer-rated group play and prosocial behaviors during unstructured free play among Chinese youth (Li et al, 2016). …”
Section: Existing Interventionsmentioning
confidence: 86%